Service utilization in community health centers in China: a comparison analysis with local hospitals - Wang Xiaohang; Dib Hassan H; Pan Xilong; Zhang Hong (BMC, 2006)
Abstract Background Being an important part of China's Urban Health Care Reform System, Community Health Centers (CHCs) have been established throughout the entire country and are presently undergoing substantial reconstruction. However, the services being delivered by the CHCs are far from reaching their performance targets. In order to assess the role of the CHCs, we examined their performance in six cities located in regions of South-East China. The purpose of this investigation was to identify the utilization and the efficiency of community health resources that are able to provide basic medical and public health services. Methods The study was approved by Peking University Health Science Center Institutional Reviewing Board (NO: IRB00001052-T1). Data were collected from all the local health bureaux and processed using SPSS software. Methods of analysis mainly included: descriptive analysis, paired T-test and one-way ANOVA. Results The six main functions of the CHCs were not fully exploited and the surveys that were collected on their efficiency and utilization of resources indicate that they have a low level of performance and lack the trust of local communities. Furthermore, the CHCs seriously lack funding support and operate under difficult circumstances, and residents have less positive attitudes towards them. Conclusion The community health service must be adjusted according to the requirements of urban medical and health reform, taking into account communities' health needs. More research is required on the living standards and health needs of residents living within the CHC's range, taking into consideration the users' needs in expanding the newly implemented service, and at the same time revising the old service system so as to make the development of CHCs realistic and capable of providing a better service to patients. Several suggestions are put forward for an attainable scheme for developing a community health service.